English Phonetics and Phonology - Kilmer, Dylan (USA: Willford Press, 2020)
The branch of Linguistics which delves into the sounds that are a part of human speech is known as Phonetics. It primarily deals with the physical properties of speech sounds or signs, along with their acoustic properties, auditory perception, physiological production and neurphysiological status. Phonology is another branch of Linguistics which deals with the systematic organization of sounds in the spoken languages.
Includes Bibliographic references and index.
Keywords: English Language-Phonetics--English Language-Phonology--English Language-Grammar